Aluminium-12wt% silicon coating prepared by thermal spraying technique: Part 1 optimization of spray condition based on a design of experiment - A. Yudee (2018)
At present, thermal spray technology is used for maintenance parts of various machines in many industries. This technology can be used to improve the surface wear resistance. Therefore, this technology can significantly reduce cost of manufacturing. Al-12wt%Si alloy is an interesting and popular material used in the automotive industry. This research studies the suitable condition for spraying of AI-12wt%Si powder. This powder was sprayed by a flame spray technique onto low carbon steel substrates. The suitable conditions for spraying can be achieved by a design of experiment (DOE) principle, which provided statistical data defined at 90% confidence. This research used control factors, which were oxygen flow rate, acetylene flow rate and spray distance. The satisfaction levels of these factors were set at 3 levels, i.e. low, medium and high, in order to determine suitable responses, which were hardness, thickness, wear rate and percentage volume fraction of porosity. It was found that the optimized condition for spraying Al-12wt%Si powder consisted of 38 ft 3/hr (1.026 m3/hr) of oxygen flow rate, 27 ft 3/hr (0.729 m3/hr) of acetylene flow rate and 58 mm of spray distance.